Multidrug-resistant Acinetobacter baumannii infection in children. (15th August 2011) - De Luca, Maia; Angelino, Giulia; Carducci, Francesca Ippolita Calò; Martino, Alessandra; Bernardi, Stefania; Bernaschi, Paola; Carletti, Michaela; D'Argenio, Patrizia; Palma, Paolo
Abstract : Acinetobacter baumannii is a Gram-negative coccobacillus causing serious nosocomial infections. The recent emergence of strains of bacteria, which are resistant to common antibiotics, has made the treatment of these infections increasingly complex. We report the case of a young patient affected by AIDS, who suffered brain toxoplasmosis and sepsis due to multidrug-resistant A baumannii . This bacterial infection was successfully treated with colistin and tigecycline. In addition, we review recent literature on this topic, from the year 2000 to date.